(untitled) (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2023)
Many of the petitions that the African Court on Human and Peoples’ Rights receives from individuals are subjected to inadmissibility objections raised by the respondent state. Such objections are most frequently raised in respect of the exhaustion of domestic remedies rule. In the Diakité case, the Court was called uponto rule on the petition of a Malian couple who, after being the victim of burglary, had filed a complaint with the Public Prosecutor’s Office. Disappointed by the slow progress in the case, the victims applied to the African Court. Can it be said that before the exercise of this right to individual petition before the African Court, the applicants had exhausted domestic remedies? The Court declared the application inadmissible for non-exhaustion of domestic remedies. In this judgment, the African Court protects an important procedural guarantee provided for under the African Charter. This judgment attests to the implacability of the rule of exhaustion of domestic remedies even if the Court is more inclined to analyse it in favour of individuals’ access to international justice.